Carl Theodor und Minerva: die Standbilder auf der Heidelberger Neckarbrücke - Prückner, Helmut (Pfälzer Heimat, 1981)
Von Conrad Linck; Alte Brücke
Keywords: Karl Theodor -- Pfalz, Kurfürst -- 1724-1799; Linck, Konrad -- 1730-1793; Heidelberg